Enhanced adaptive reconfiguration for optimizing power generation and switching efficiency in PV arrays under PSC - D. Manimegalai; Kandadai Nagaratnam Srinivas; Gayathri Monicka Subarnan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
Photovoltaic (PV) arrays suffer significant power losses under partial shading conditions (PSC), which can degrade system performance. This paper proposes a novel weighted objective function that balances power output maximization with switching action minimization during dynamic PV array reconfiguration. An enhanced firebug swarm optimization (FSO) algorithm is employed to optimize this function efficiently. Simulation results under five shading patterns demonstrate approximately 6% improvement in power output over conventional methods, while also reducing the number of switch operations. The proposed approach enhances energy yield and extends device lifespan, offering a robust solution for real-time PV optimization under PSC.